Numerical prediction on turbine blade internal tip cooling with pin-fin and dimple/protrusion structures. (1st November 2016) - Zhang, Di; Jing, Qi; Xie, Yonghui; Shen, Zhongyang
ABSTRACT: Effective cooling techniques are required urgently because of high thermal loads on the blade tip region. The 180° turning bend is recognized to perform well in heat transfer on a blade tip. The thermal fluid-solid coupling models of the internal tip region with pin-fin-dimples/protrusions are established in the present paper. The local flow characteristics near the 180° turning bend, average Nu/Nu 0, and the friction loss on the impingement surfaces are obtained. The local flow field near the tip surface is influenced by the 180° turning bend, where the fluid impingement, cross-flow convection and deflection of the secondary flow exist. The average Nu of dimple/protrusion structures is increased by 3.2%-31.5% comparing to that of a smooth case. After arranging pin-fin-dimple/protrusion, the average Nu is increased to 31.2%-127.3%, much higher than dimple/protrusion structures. Furthermore, the arrangement of pin-fin-dimple/protrusion brings no significant increase in the friction, which indicates an efficient heat transfer structure with little resistance.